LATENT STRUCTURE OF STANDARD INDICATORS OF SITUATIONAL EFFECTIVENESS IN BASKETBALL IN BOSNIAN LEAGUE 6 - Vlatko Šeparović; Amir Nuhanović (Sport Scientific And Practical Aspects, 2025)
The aim of this research is to determine latent structure of basketball by applying Factor analysis (alpha method) on 15 standard indicators of situational effectiveness (FIBA), on the sample of 30 games in Bosnian Basketball League 6 for the champion of Bosnia and Herzegovina. Initial co-ordinate system is transformed by nonorthogonal rotation according to Oblimin criterion. By analyzing situational indicators that influence successfulness of the strongest basketball teams that reach the playoffs of Bosnian League 6 in battle for the championship trophy, four latent dimensions which present the structure of basketball have been identified in this research. These dimensions are: effectiveness of scoring from close range, effectiveness of scoring from mid-range, overall defensive effectiveness of players and specific defensive agility. For a complete analysis of the structure it is necessary to expand the basis of situational indicators